A Novel Cell Death Gene Acts to Repair Patterning Defects in Drosophila melanogaster. Issue 2 (1st June 2014) - Tanaka, Kentaro M; Takahashi, Aya; Fuse, Naoyuki; Takano-Shimizu-Kouno, Toshiyuki
Abstract: Cell death is a mechanism utilized by organisms to eliminate excess cells during development. Here, we describe a novel regulator of caspase-independent cell death, Mabiki ( Mabi ), that is involved in the repair of the head patterning defects caused by extra copies of bicoid in Drosophila melanogaster . Mabiki functions together with caspase-dependent cell death mechanisms to provide robustness during development.